YF-H-2015005, a CXCR4 Antagonist, for the Mobilization of Hematopoietic Stem Cells in Non-Hodgkin Lymphoma Patients: A Randomized, Controlled, Phase 3 Clinical Trial - Liu, Weiping; Li, Yufu; Wang, Quanshun; Su, Hang; Ding, Kaiyang; Shuang, Yuerong; Gao, Sujun; Zou, Dehui; Jing, Hongmei; Chai, Ye; Zhang, Yicheng; Liu, Lihong; et al. (Frontiers in Medicine, 2021)
Background: YF-H-2015005, a novel CXCR4 antagonist, has been proven to increase the quantities of circulating hematopoietic stem cells (HSCs), which results in an adequate collection of HSCs in non-Hodgkin lymphoma (NHL) patients. Methods: This was a multicenter, double-blind, randomized (1:1), placebo-controlled phase III clinical trial. All patients received granulocyte colony-stimulating factor (G-CSF) for up to 8 consecutive days. YF-H-2015005 or placebo was administrated on the evening of day 4 and continued daily for up to 4 days. Apheresis was conducted 9-10 hours after each dose of YF-H-2015005 or placebo. The primary endpoint was the proportion of NHL cases procuring ≥5×106/kg CD34+ HSCs within ≤4 apheresis sessions. Results: In total, 101 patients with NHL were enrolled. The proportions of patients achieving primary endpoint were 57% and 12% in YF-H-2015005 and placebo groups, respectively (P<0.001). Moreover, a higher proportion of YF-H-2015005-treated patients reached a minimum target collection of ≥2×106/kg CD34+ HSCs in ≤4 apheresis days compared to placebo-treated patients (86% vs. 38%, P<0.001). Furthermore, the median time to collect ≥2 or 5×106/kg CD34+ HSCs were 1 day and 3 days in YF-H-2015005-treated patients, while 4 days and not reached in placebo-treated patients. No severe treatment emergent adverse events were observed in both YF-H-2015005 treatment and placebo groups. Conclusions: YF-H-2015005 plus G-CSF regimen was a tolerable combination with high efficacy, which might be used to rapidly mobilize and collect HSCs in NHL patients.